Haze aerosol optical thickness (HAOT) retrieval of peninsular Malaysia using remote sensing technique [electronic resource] - Muhamad Faridzul Adli Zakaria, 1991-; Md. Latifur Rahman Sarker, supervisor 595753; Fakulti Geoinformasi dan Harta Tanah 555724 (2014)
Project Paper (Sarjana Muda Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2014